Accelerating Nitrate Electroreduction to Ammonia via Metal–Support Interactions in Ni-WS2 Catalysts - Lv, Jiangnan; Yang, Qianwen; Liang, Tingting; Sun, Xiaoting; Rong, Wanting; Dai, Qiqi; Gao, Yizhi; Wang, Lanfang; Xu, Xiaohong; Liu, Yang (Journal of the American Chemical Society, 2025)
Electrocatalytic nitrate reduction reaction (NO3 –RR) is a promising route for both treating NO3 –-containing wastewater and enabling sustainable ammonia (NH3) synthesis. While two-dimensional (2D) transition metal dichalcogenides (TMDs) catalysts have been widely investigated as catalysts in various electrocatalytic reactions, their practical application in NO3 –RR remains hindered by inherently sluggish kinetics and insufficient stability. Metal–support interaction (MSI), which enhances charge transfer and stabilizes catalytic sites, offers a compelling strategy to address these challenges. Herein, we design an MSI-driven Ni-WS2 catalyst via a two-step strategy. The Ni-WS2 catalyst demonstrates outstanding NO3 –RR performance, achieving a Faradaic efficiency of 91.7% at −0.3 VRHE with an NH3 yield rate of 23.3 mg h–1 cm–2 at −0.7 VRHE. Significantly, the Ni-WS2 catalyst maintained an exceptional stability in a membrane electrode assembly (MEA), sustaining ≈32 mg h–1 cm–2 NH3 production over 100 h, surpassing most previously reported TMD-based catalysts. Density functional theory (DFT) calculations reveal that MSI between Ni metal and WS2 support induces interfacial charge redistribution, optimizes adsorption energy of key intermediates and lowers the energy barrier for the rate-determining step (*NH2 → *NH3). Furthermore, the Zn-NO3 – battery assembled with Ni-WS2 cathode exhibits remarkable performance. This work advances a two-step synthesis strategy for high-performance NO3 –RR electrocatalysts through targeted MSI modulation.